Implementation of Subsidized Housing Transfer Regulations Before Five Years: An Empirical Study on Subsidized Housing in Tangerang: Implementasi Pengaturan Peralihan Rumah Subsidi Sebelum Lima Tahun: Studi Empiris pada Perumahan Subsidi di Tangerang - Putri, Ananda Salasa; Herlindah; Wicaksono, Setiawan (WARKAT, 2025)
Subsidized housing is a government-initiated housing program aimed at providing decent, affordable housing for low-income communities (MBR) to support family welfare. Article 55 paragraph (1) letter b of Law Number 6 of 2023, which ratifies Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation, clearly prohibits the transfer of ownership of subsidized houses by recipients within five years. However, field findings indicate that early transfers still occur, both covertly and through informal agreements. This study aims to examine the implementation of this legal provision, specifically in subsidized housing in the Tangerang region. The research uses an empirical legal method with a sociological juridical approach. The findings show that the implementation has not been optimal. Legal violations persist, influenced by weak oversight and limited public understanding of the legal restrictions on subsidized housing transfers. Additional challenges include lack of inter-agency coordination and weak law enforcement. Recommended solutions include enhancing legal education for beneficiaries, strengthening supervision by relevant institutions, and developing a digital-based monitoring and reporting system to prevent future violations.